Solution and stability of a new reciprocal type functional equation (Balkan Journal of Applied Mathematics and Informatics, 2022)
The aim of this paper is to obtain the general solution of a reciprocal functional equation of the form\begin{equation*}\frac{1}{f(x+u,y+v)}=\frac{1}{2f(2x+y,2u+v)}+\frac{1}{2f(y,v)}\end{equation*}and investigate its generalized Hyers-Ulam stability.
Keywords: Reciprocal functional equation, Hyers-Ulam stability, general solution, direct method